2009
DOI: 10.1002/mop.24761
|View full text |Cite
|
Sign up to set email alerts
|

Minimum loss condition of a bent rectangular hollow waveguide

Abstract: The leakage loss of a hollow dielectric waveguide is analyzed analytically and numerically. A minimum loss condition of a bent rectangular hollow waveguide is derived in terms of the refractive index of the cladding using the perturbation method. The validity of the derived minimum loss condition is confirmed by the beam‐propagation method. © 2009 Wiley Periodicals, Inc. Microwave Opt Technol Lett 51: 2901–2902, 2009; Published online in Wiley InterScience (www.interscience.wiley.com). DOI 10.1002/mop.24761

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…It is found that the loss tends to decrease as is decreased, since the core area becomes larger. To interpret the behavior of the loss in more detail, we should recall the loss properties in a hollow slab waveguide, which has a minimum loss condition of for the transverse-magnetic (TM) mode [11]. In Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is found that the loss tends to decrease as is decreased, since the core area becomes larger. To interpret the behavior of the loss in more detail, we should recall the loss properties in a hollow slab waveguide, which has a minimum loss condition of for the transverse-magnetic (TM) mode [11]. In Fig.…”
Section: Discussionmentioning
confidence: 99%